Monoclonal Antibody Therapy in a Vaccine Breakthrough SARS-CoV-2 Hospitalized Delta (B.1.617.2) Variant Case. (September 2021) - Connor, Bradley A; Couto-Rodriguez, Mara; Barrows, Joseph E; Gardner, Morgan; Rogova, Marina; O'Hara, Niamh B.; Nagy-Szakal, Dorottya
Highlights: Vaccine breakthrough of father and son living in separate households Delta (B.1.617.2) variant vaccine breakthrough cases One case was severe enough to lead to hospitalization Despite high titer of anti-spike IgG, bamlanivimab/etesevimab provided resolution of symptoms ABSTRACT: We present two Delta (B.1.617.2) vaccine breakthrough individuals, a father and son living in separate households. The older, 63-year-old patient's symptoms were severe enough to require hospitalization. Despite having a high titer of anti-spike IgG in his serum, his symptoms resolved within 24 hours following monoclonal antibody (bamlanivimab/etesevimab) therapy.